2012
DOI: 10.3389/fnbeh.2012.00078
|View full text |Cite
|
Sign up to set email alerts
|

The role of orexins/hypocretins in alcohol use and abuse: an appetitive-reward relationship

Abstract: Orexins (hypocretins) are neuropeptides synthesized in neurons located in the lateral (LH), perifornical, and dorsomedial (DMH) hypothalamus. These neurons innervate many regions in the brain and modulate multiple other neurotransmitter systems. As a result of these extensive projections and interactions orexins are involved in numerous functions, such as feeding behavior, neuroendocrine regulation, the sleep-wake cycle, and reward-seeking. This review will summarize the literature to date which has evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 110 publications
(154 reference statements)
1
18
0
Order By: Relevance
“…Pharmacological studies demonstrate that central injection of MCH increases ethanol intake (Duncan et al, 2005, Morganstern et al, 2010b) while an MCH antagonist reduces it (Cippitelli et al, 2010), and endogenous expression of MCH is greater in rats prone to consuming excess ethanol (Morganstern et al, 2010b). Clinical studies also provide support for a role of MCH in mediating the rewarding properties of ethanol (DiLeone et al, 2003, Duncan et al, 2005, Kim et al, 2012). In addition, there is evidence that the CCL2/CCR2 signaling pathway itself has a role in controlling ethanol consumption, with studies showing a deletion of the CCR2 gene in males and CCL2 gene in females to reduce the drinking of ethanol (Blednov et al, 2005).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Pharmacological studies demonstrate that central injection of MCH increases ethanol intake (Duncan et al, 2005, Morganstern et al, 2010b) while an MCH antagonist reduces it (Cippitelli et al, 2010), and endogenous expression of MCH is greater in rats prone to consuming excess ethanol (Morganstern et al, 2010b). Clinical studies also provide support for a role of MCH in mediating the rewarding properties of ethanol (DiLeone et al, 2003, Duncan et al, 2005, Kim et al, 2012). In addition, there is evidence that the CCL2/CCR2 signaling pathway itself has a role in controlling ethanol consumption, with studies showing a deletion of the CCR2 gene in males and CCL2 gene in females to reduce the drinking of ethanol (Blednov et al, 2005).…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, in a recent report (Chang et al, 2012), we demonstrated that exposure to ethanol during gestation, at low-to-moderate doses (1 or 3 g/kg/day) that elevate blood ethanol concentration (BEC) to <100 mg/dL, markedly stimulates neurogenesis and increases the density and long-term expression of the orexigenic peptides, OX in the LH as well as galanin and enkephalin in the hypothalamic paraventricular nucleus (Chang et al, 2012). Although yet to be investigated, recent studies of MCH showing its role in mediating the rewarding and motivating properties of ethanol (DiLeone et al, 2003, Duncan et al, 2005, Kim et al, 2012) suggest that neurons expressing this peptide are likely to be similarly affected by gestational ethanol and, in turn, to contribute significantly to the phenomenon of excess alcohol drinking.…”
Section: Introductionmentioning
confidence: 99%
“…Orexin has also been implicated in nonfood rewards such as addictive drugs (Harris et al, 2005;Harris and Aston-Jones, 2006;Aston-Jones et al, 2010;Smith et al, 2010b;Kim et al, 2012;Mahler et al, 2012). Involvement in drug rewards raises the possibility that the VP orexin hotspot identified here might also have a role in generating intense drug pleasures, and possibly of other non-ingestive sensory rewards.…”
Section: Circuit and Clinical Implicationsmentioning
confidence: 81%
“…The mechanisms of these disruptions may include alterations to the expression of tyrosine hydroxylase and dopamine firing in the VTA (Coque et al, 2011; McClung et al, 2005), or altered dopamine levels and D1 to D2 receptor ratio in the nucleus accumbens (Hampp & Albrecht, 2008). Animal models have uncovered that orexin, a neuropeptide involved in the homeostatic regulation of sleep, serves to modulate both circadian gene function and mesolimbic pathways (Belle et al, 2014; Kim, Brown, & Lawrence, 2012). Furthermore, circadian gene mutants often demonstrate altered reward behavior, such as increased preference for alcohol or hypersensitization to cocaine (McClung et al, 2005; Spanagel et al, 2005).…”
Section: Reward As a Mechanismmentioning
confidence: 99%